Pengaruh perbedaan kadar salinitas terhadap daya tetas telur tiram mutiara (Pinctada maxima) di Teluk Kupang - Mandosa, Wolfhelmus A; Linggi, Yulianus; Santoso, Priyo (Nusa Cendana University, 2023)
Pearl oysters (Pinctada maxima) are one of the favorite marine species with very potential selling value. P. maxima in Indonesian waters is known to produce quite large pearls. In the breeding process, temperature and salinity are the main factors in egg hatching. Therefore, the aim of this research is to determine the effect of differences in salinity levels on the hatchability of mutiata oyster (P. maxima) eggs in Kupang Bay. This research was carried out using a Completely Randomized Design (CRD) method, where there were 3 treatments, namely 28 ppt, 31 ppt, 34 ppt, with 3 replications. The results obtained were that the use of different salinities had no significant effect on egg hatchability. However, based on research results, the highest value was 31 ppt salinity with a value of 66.10%.